Artificial cavities and substrates for cavity-nesting birds in Neotropical urban environments: A novel resource or the last opportunity to breed? - Sandoval Vargas, Luis Andrés (2021)
Urban development reduces the abundance of most natural resources for some birds but also provides new opportunities for others. One group that is more likely affected by urban development is the cavity-nesting species (primary excavators and cavity-adopters), because the main substrates used for nesting, such as dead trees or dirt banks, are frequently removed for security or aesthetic reasons. However, urban development also provides artificial resources that may be used for some cavity-nesting birds such as wooden posts, poles, pipes, holes in house roofs, or building crevices. How cavity-nesting species use these new artificial resources for nesting is poorly understood. Our goal is to provide information on the use of artificial cavities and artificial substrates in urban and human-altered areas for cavity-nesting birds. We opportunistically collected observations of the use of those cavities and substrates from 2003 to 2019 in Costa Rica and found that 20.2% of the 94 Costa Rican bird species that are known to nest in wooden cavities and 9.5% of the 21 Costa Rican bird species that are known to nest in burrows use artificial cavities or artificial substrates for nesting. Although our observations showed that some species are capable of responding to the reduction of natural substrates or cavities in urban habitats through the use of artificial structures, the reproductive success of these birds is still unknown. Received 22 November 2019. Accepted 1 October 2021.